The development of Sustainable Food Systems based on climate smart agriculture and circular principles - Moata, Melinda R.S.; Bunga, Jaqualine A. (State Agricultural Polytechnic of Kupang, Indonesia, 2023)
The agriculture sector plays an important role for food security and national income. However, climate change and business models have challenged the development in agriculture, especially in limitedresource regions like Nusa Tenggara Timur, Indonesia. Therefore, a study on climate-smart agriculture, value chains, gender, and partnerships is needed to develop a business model, especially for horticulture products. This research applied observation, survey, and interview methods to four elements (climate adaptation, value chain, inclusive entrepreneurship, and partnership). Each element was analyzed using content and social network analyses. The output of this research provides innovation for the transformation of agri-food systems through climate-resilient, good agricultural practices, and land and water management, competitive circular business models, and circular supply chains, gender and youth awareness, and Pentahelix collaboration. The outcome of this research is improving food security through partnership with a focus on the development of sustainable food systems based on climate-smart agriculture and circular principles with an integrated and collaborative approach.